2014
DOI: 10.1007/s00442-014-3091-7
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between plant life form and fungal traits of arbuscular mycorrhizal fungi determine the symbiotic community

Abstract: Arbuscular mycorrhizal (AM) fungi have traditionally been considered generalist symbionts. However, an increasing number of studies are pointing out the selectivity potential of plant hosts. Plant life form, determined by plant life history traits, seems to drive the AM fungal community composition. The AM fungi also exhibit a wide diversity of functional traits known to be responsible for their distribution in natural ecosystems. However, little is known about the role of plant and fungal traits driving the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 64 publications
0
31
1
Order By: Relevance
“…The fact that the five target plant species, chosen because they are the most common at the study site, have similar functional characteristics could minimize the differences in terms of AMF community composition in agreement with previous studies (Yang et al 2012). A host plant effect could have been more easily detected if a group of more ecologically dissimilar plants had been selected, according to other studies developed in the same area (López-García et al 2014a).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The fact that the five target plant species, chosen because they are the most common at the study site, have similar functional characteristics could minimize the differences in terms of AMF community composition in agreement with previous studies (Yang et al 2012). A host plant effect could have been more easily detected if a group of more ecologically dissimilar plants had been selected, according to other studies developed in the same area (López-García et al 2014a).…”
Section: Discussionmentioning
confidence: 71%
“…However, some studies have found preferences of certain host plants for certain fungal species, indicating that the host partner can influence the AMF community associated to it (Helgason et al 2002;Vandenkoornhuyse et al 2003;Li et al 2010). Nowadays, it is increasingly accepted that the mycorrhizal symbiotic assemblages are mainly driven by the plant ecological group rather than by the plant species identity (Öpik et al 2009;Yang et al 2012;López-García et al 2014a). In any case, the relationship between AMF and host plant species could be explained by functional differences among AMF taxa, especially in relation to the effect they have on their hosts (Munkvold et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…The minor seasonal variation apparent in our data might be related to the fact that all but three of the plant species were perennial. Furthermore, seasonal variability in AM fungal community composition has been shown to be relatively low in herbaceous plants (López‐García, Azcón‐Aguilar, & Barea, ), which represent the majority of the plant community in this study.…”
Section: Discussionmentioning
confidence: 75%
“…These results indicated that the AMF recruitment preferences by C. ambrosioides differed among sampling sites. Several explanations for the differences in the AMF present in the roots and rhizosphere soils of the same plant have been proposed, including different AMF life strategies, differential sporulation dynamics, and seasonal changes in the AMF community505152.…”
Section: Discussionmentioning
confidence: 99%